A feira de Olney São Paulo: imagens de “como nasce uma cidade” - Bastos, Hosana Caroline Brandão (2015)
This article deals with the moving image in the film sequences Como Nasce Uma Cidade as a device to analyze Feira de Santana, which was filmed by Olney São Paulo in 1973, and so understand the history of the city construction from his filmic plans and parse the figure of Lucas da Feira and the presence of black people, and also grasp the relationship between modernity and tradition. Therefore, we embarked on theoretical and methodological approach to film analysis, from the shooting script of the film through the FRAPS program, which allowed us to capture scenes in isolation, and in that way, we followed in the interpretation of such images, which present patent and latent meanings in speech imagery built by Olney on his Feira de Santana, the result of his concerns and paths from backlands to the world, exposing some shortcomings and inset of local history and memory.